Xylem Cell Wall Formation in Pioneer Roots and Stems of Populus trichocarpa (Torr. & Gray) - Marzec-Schmidt, Katarzyna; Ludwików, Agnieszka; Wojciechowska, Natalia; Kasprowicz-Maluśki, Anna; Mucha, Joanna; Bagniewska-Zadworna, Agnieszka (Frontiers in Plant Science, 2019)
Regulation of gene expression, as determined by the genetics of the tree species, is a major factor in determining wood quality. Therefore, the identification of genes that play a role in xylogenesis is extremely important for understanding the mechanisms shaping the plant phenotype. Efforts to develop new varieties characterized by higher yield and better wood quality will greatly benefit from recognizing and understanding the complex transcriptional network underlying wood development. The present study provides a detailed comparative description of the changes that occur in genes transcription and the biosynthesis of cell-wall-related compounds during xylogenesis in Populus trichocarpa pioneer roots and stems. Even though, results of microarray analysis indicated that only approximately 10% of the differentially expressed genes were common to both organs, many fundamental mechanisms were similar; e.g. the pattern of expression of genes involved in the biosynthesis of cell wall proteins, polysaccharides and lignins. Chromatography GC-TOF-MS shows that the composition of monosaccharides was also very similar, with an increasing amount of xylose building SCW hemicellulose and pectins especially in the stems. While hemicellulose degradation was typical for stems, possibly due to the intensive level of cell wall lignification. Notably, the main component of lignins in roots were guiacyl units, while syringyl units were dominant in stems, where fibers are especially needed for support. Our study is the first comprehensive analysis, at the structural and molecular level, of xylogenesis in uner- and aboveground tree parts, and clearly reveals the great complexity of molecular mechanisms underlying cell wall formation and modification during xylogenesis in different plant organs.